Time trend in suicide mortality in the state of Bahia - Carmo, Érica Assunção; Ribeiro, Bárbara Santos; Nery, Adriana Alves; Casotti, Cezar Augusto [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: To analyze the time trend in suicide mortality in the state of Bahia according to gender and age range, in the 1996-2013 period. Methods: A time series study based on data from Brazil’a Mortality Information System (SIM), with trend analysis that uses Prais-Winsten regression. Results: Of the 5,393 people who died from suicide in Bahia, 81.4% (n = 4632) were men and 46% (n = 2619) were aged 20-39 years. As to the means used, 58.6% (n = 3336) of the deaths were due to intentional self-harm by hanging and strangulation, followed by self-poisoning by pesticides and chemicals (15.9% / n = 906). There was an increasing trend in the coefficient of mortality by suicide in the State for both genders and for the groups of 20 to 39 years, 40 to 59 years and 60 years or more. Conclusion: Suicide in Bahia predominates among young males, with an increasing trend of the total coefficient and in the different population groups.
Tendencia temporal de la mortalidad por suicido en el estado de Bahía
Tendência temporal da mortalidade por suicídio no estado da Bahia
Keywords: Ecological studies; Information systems; Mortality; Suicide; Time series studies